The Electrical Power Engineering Profession in Sweden - Overview and Milestones - Eriksson, S.J.A. (2009 IEEE Conference on the History of Technical Societies, 2009)
Sweden is highly electrified and the electrical power engineers have had an important role in this development. Fundamental for these engineers is their education, their working experience, and their professional network. The Swedish development over time of these factors is highlighted. Organizations for engineers are essential parts of their network and the country has a long tradition in this respect. It started with local and national assemblies, but international organizations have successively grown in importance.